Robotic transmural ablation of bladder tumors using high‐intensity focused ultrasound: Experimental study. (1st April 2016) - de Castro Abreu, Andre Luis; Ukimura, Osamu; Shoji, Sunao; Leslie, Scott; Chopra, Sameer; Marien, Arnaud; Matsugasumi, Toru; Dharmaraja, Arjuna; Wong, Kelvin; Zaba, Natalie; Ma, Yanling; Desai, Mihir M; et al.
Abstract : Objectives: To evaluate the feasibility of robot‐assisted laparoscopic high‐intensity focused ultrasound for targeted, extravesical, transmural, full‐thickness ablation of intact bladder wall and tumor. Methods: In three fresh cadavers and one acute porcine model, the transperitoneal robotic approach was used to mobilize the bladder and create a midline cystotomy. "Mimic" bladder tumors (2 tumors/case) were created by robotically suturing a piece of striated muscle (2.5 × 2.5 cm) to the luminal, urothelial surface of the bladder wall. The cystotomy was suture‐repaired and bladder distended with 250 mL saline. A laparoscopic high‐intensity focused ultrasound probe was robotically placed extravesically in direct contact with the serosal surface of the bladder wall to image the "mimic" tumor. Targeted, transmural, full‐thickness high‐intensity focus ultrasound ablation of the "mimic" tumor and adjacent bladder was carried out under real‐time ultrasound and robotic monitoring. Untreated areas of the bladder served as a comparison. Post‐procedure, gross and microscopic examinations were carried out. Results: Laparoscopic high‐intensity focused ultrasound ablation was feasible for all "mimic" tumors (100%). Real‐time ultrasound clearly visualized the "mimic" tumor. Simultaneous display of the pre‐planning and real‐time treatment ultrasound images confirmed targeting precision. Mean operative room times for ultrasound localization, laparoscopic high‐intensity focused ultrasound probe coupling, high‐intensity focus ultrasound ablation, and total procedure were 3, 5, 6 and 60 min, respectively. On necropsy, no thermal/mechanical injuries occurred to the untreated bladder wall, adjacent organs or ureters. Gross inspection distinguished the treated from untreated areas. Histopathology confirmed sharply demarcated thermal coagulative necrosis and shrinkage effects between the treated and untreated areas. Conclusions: Laparoscopic extravesical high‐intensity focus ultrasound for transmural, full‐thickness targeted ablation of intact bladder wall and tumor is feasible. This has implications for bladder‐sparing surgery in select patients with solitary muscle‐invasive bladder cancer.